Politik und Angst: Oder: homo neuroticus und der Spuk nationaler Souveränität - Bargetz, Brigitte (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2018)
What are the contemporary conditions of Western modern democracies that make a politics of fear so successful at this present moment? In this article, the author analyzes the relationship between politics and fear in order to move beyond a simple instrumentalization thesis. Focusing on two perspectives: the view of state sovereignty and the phenomenon of neurosis, the author argues that the contemporary Western modern politics of fear can be understood as an expression of a crisis of state sovereignty, which becomes apparent in the nation state as well as in a new mode of political subjectivation. It is a ghostly sovereignty that finds both a form and an addressee in a neurotic subject.